Nonlinear Optical Studies of Gold Nanoparticle Films - Anuradha Rout; Ganjaboy S. Boltaev; Rashid A. Ganeev; Yue Fu; Sandeep Kumar Maurya; Vyacheslav V. Kim; Konda Srinivasa Rao; Chunlei Guo (Nanomaterials, 2019)
Gold films are widely used for different applications. We present the results of third- and high-order nonlinear optical studies of the thin films fabricated from Au nanoparticle solutions by spin-coating methods. These nanoparticles were synthesized by laser ablation of bulk gold in pure water using 200 ps, 800 nm pulses. The highest values of the nonlinear absorption coefficient (9 × 10−6 cm W−1), nonlinear refractive index (3 × 10−11 cm2 W−1), and saturation intensity (1.3 × 1010 W cm−2) were achieved using 35 fs, 400 nm pulses. We also determined the relaxation time constants for transient absorption (220 fs and 1.6 ps) at 400 nm. The high-order harmonic generation was studied during propagation of 35 fs, 800 nm pulses through the plasma during the ablation of gold nanoparticle film and bulk gold. The highest harmonic cutoff (29th order) was observed in the plasma containing gold nanoparticles.